2003
DOI: 10.1002/jrs.1001
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectra of putrescine, spermidine and spermine polyamines and their N‐deuterated and N‐ionized derivatives

Abstract: The experimental and calculated Raman spectra of the N-hydrogenated and N-deuterated biogenic polyamines putrescine, spermidine and spermine and of their N-hydrogenated and N-deuterated hydrochloride salts in the 2000-3400 cm −1 spectral region (at distinct temperatures) are reported and analysed. A complete assignment of the N-H, C-H and N-D stretching modes is carried out, in the light of both steric and hydrogen-bonding interactions on the conformational behaviour of these systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…31 These chelates, containing the biogenic polyamines spermidine (H 2 N(CH 2 ) 3 NH(CH 2 ) 4 NH 2 ) and spermine (H 2 N(CH 2 ) 3 NH(CH 2 ) 4 NH(CH 2 ) 3 NH 2 ) as bridging linkers, differ in the metal coordination pattern, as well as in the number and geometry of their leaving groups. This is intended as an interactive structureactivity research work, the structural characteristics of the compounds tested (determined in a concurrent study through physical-chemical methods [32][33][34][35][36] ) being changed according to their antitumor activity evaluation. Thus, the results obtained from these studies may hopefully contribute to a better understanding of the molecular basis of toxicity (i.e., of the biochemical processes underlying the antiproliferative effect of these kinds of compounds), which is fundamental in order to design new cytostatic agents with improved therapeutical properties.…”
Section: Introductionmentioning
confidence: 99%
“…31 These chelates, containing the biogenic polyamines spermidine (H 2 N(CH 2 ) 3 NH(CH 2 ) 4 NH 2 ) and spermine (H 2 N(CH 2 ) 3 NH(CH 2 ) 4 NH(CH 2 ) 3 NH 2 ) as bridging linkers, differ in the metal coordination pattern, as well as in the number and geometry of their leaving groups. This is intended as an interactive structureactivity research work, the structural characteristics of the compounds tested (determined in a concurrent study through physical-chemical methods [32][33][34][35][36] ) being changed according to their antitumor activity evaluation. Thus, the results obtained from these studies may hopefully contribute to a better understanding of the molecular basis of toxicity (i.e., of the biochemical processes underlying the antiproliferative effect of these kinds of compounds), which is fundamental in order to design new cytostatic agents with improved therapeutical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, to the best of the authors' knowledge, only two studies can be found in the literature on the ab initio assignment of the Raman spectra of such molecules, and even these are restricted to the NÀH and CÀH stretching modes. [38,39] The present work is aimed at the study of the homologous series of a,w-diamine dihydrochlorides of general formula [H 3 N(CH 2 ) n NH 3 )] 2 + ·2Cl À (n = 2-10 and n = 12) in the solid state. In the absence of any theoretical report on these polycationic molecules, the primary concern was the selection of an adequate molecular model for the representation of such systems.…”
Section: Introductionmentioning
confidence: 99%
“…The homologous series of the linear α,ω-diamines [H 2 N(CH 2 ) n NH 2 ] (n = 2-10, n = 12) and the tri-and tetramines spermidine and spermine ( Figures 1A-1C) were studied in order to achieve a thorough knowledge of their structural preferences, both for their unprotonated and Nprotonated forms [24][25][26][27][28][29][30][31][32][33]. Several theoretical molecular models were proposed for an accurate representation of these linear polyamines, yielding the best possible agreement with the experimental data (both vibrational spectroscopy results and reported X-ray structures).…”
Section: Aliphatic Linear Polyaminesmentioning
confidence: 99%